Occurrence of bats in protected areas of Nepal: An update on species richness and distribution records - Thapa, Sanjan; Dahal, Dibya Raj; Ghimire, Rameshwor; Baral, Rishi; Yadav, Bhupendra; Lamichhane, Babu Ram; Dahal, Badri Vinod; Poudyal, Laxman Prasad; Yu, Wenhua; Yi, Wu (Nepalese Journal of Zoology, 2021)
Bat surveys in 20 Protected Areas (PAs) of Nepal are sporadic and/or had targeted purposively a few localities, therefore, bat diversity from the PAs is yet to be explored. Bat species richness in PAs from two reviews until 2011 are inconsistent. In total, seven surveys have been undertaken in six PAs since 2011. Hence, an update and revision on chiropteran account from the PAs of Nepal is warranted. We reviewed available literatures and museum collection records, and further collated and plotted bat occurrence coordinates into the country and mapped them. In total, 44 of 53 bat species in Nepal have been recorded from 12 PAs. Annapurna Conservation Area (ACA) reports highest species richness (22) followed by Shivapuri Nagarjun National Park and Buffer Zone (SNNP & BZ) (15), Makalu Barun National Park and Buffer Zone (MBNP & BZ) (14) and Chitwan National Park and Buffer Zone (CNP & BZ) (13). In contrast, survey localities are more in CNP & BZ (12), ACA and SNNP & BZ (equally 11) and MBNP & BZ (10). Species richness increased proportionately with higher survey efforts and including more habitat types in respective PAs. Three species: Rhinolophus ferrumequinum, Rh. pearsonii and Rh. sinicus are recorded from six out of 12 PAs. Pipistrellus javanicus (12), Hipposideros armiger (10), Cynopterus sphinx (9) and Rh. sinicus (9) are recorded from maximum number of surveyed localities in the PAs. All the PAs have limited occurrence records. Therefore, intensive surveys are recommended for understanding actual chiropteran diversity to the PAs of Nepal.